Soil data from two permafrost cores near Utqiagvik, Alaska - Dolle, Madina Lucia; Laurent, Mélissa; Vollmer, Jonas; Treat, Claire C (PANGAEA, 2025)
The dataset reports soil data of soil samples sourced from two permafrost cores taken in April 2022 near Utqiagvik, Alaska, USA. For one half of both permafrost cores, the upper meter was subsampled into four layers each. From each layer, a small part was used for soil parameter analysis and a bigger part was used for an incubation (see doi:10.1594/PANGAEA.969148). For the soil parameter analysis, pore water was extracted after thawing the samples (n = 8) to measure pH, electrical conductivity and dissolved organic matter. Afterwards, remaining sediment was freeze-dried and the parameters TC, TOC, TN and delta C13 were determined. Additional pore water samples were used to determine SO4 and Cl content.
Keywords: Alaska; coast; Drained Lake Basin; Permafrost; permafrost soil; salt; salt-affected soils; Salt water; Uplands